Billing and payment of commercial and Medicaid health plan adult vaccination claims in Michigan since the Affordable Care Act. Issue 45 (23rd October 2019) - Goodman, Robert M.; Bridges, Carolyn B.; Kim, David; Pike, Jamison; Rose, Angela; Prosser, Lisa A.; Hutton, David W.
Abstract: Background: Provider concern regarding insurance non-payment for vaccines is a common barrier to provision of adult immunizations. We examined current adult vaccination billing and payment associated with two managed care populations to identify reasons for non-payment of immunization insurance claims. Methods: We assessed administrative data from 2014 to 2015 from Blue Care Network of Michigan, a nonprofit health maintenance organization, and Blue Cross Complete of Michigan, a Medicaid managed care plan, to determine rates of and reasons for non-payment of adult vaccination claims across patient-care settings, insurance plans, and vaccine types. We compared commercial and Medicaid payment rates to Medicare payment rates and examined patient cost sharing. Results: Pharmacy-submitted claims for adult vaccine doses were almost always paid (commercial 98.5%; Medicaid 100%). As the physician office accounted for the clear majority (79% commercial; 69% Medicaid) of medical (non-pharmacy) vaccination services, we limited further analyses of both commercial and Medicaid medical claims to the physician office setting. In the physician office setting, rates of payment were high with commercial rates of payment (97.9%) greater than Medicaid rates (91.6%). Reasons for non-payment varied, but generally related to the complexity of adult vaccine recommendations (patient diagnosis does not match recommendations) or insurance coverage (complex contracts, multiple insurance payers). Vaccine administration services were also generally paid. Commercial health plan payments were greater for both vaccine dose and vaccine administration than Medicare payments; Medicaid paid a higher amount for the vaccine dose, but less for vaccine administration than Medicare. Patients generally had very low (commercial) or no (Medicaid) cost-sharing for vaccination. Conclusions: Adult vaccine dose claims were usually paid. Medicaid generally had higher rates of non-payment than commercial insurance.